Coronary low-attenuation plaque and high-sensitivity cardiac troponin. Issue 9 (11th January 2023) - Meah, Mohammed N; Wereski, Ryan; Bularga, Anda; van Beek, Edwin J R; Dweck, Marc R; Mills, Nicholas L; Newby, David E; Dey, Damini; Williams, Michelle Claire; Lee, Kuan Ken
Abstract : Objective: In patients with acute chest pain who have had myocardial infarction excluded, plasma cardiac troponin I concentrations ≥5 ng/L are associated with risk of future adverse cardiovascular events. We aim to evaluate the association between cardiac troponin and coronary plaque composition in such patients. Methods: In a prespecified secondary analysis of a prospective cohort study, blinded quantitative plaque analysis was performed on 242 CT coronary angiograms of patients with acute chest pain in whom myocardial infarction was excluded. Patients were stratified by peak plasma cardiac troponin I concentration ≥5 ng/L or <5 ng/L. Associations were assessed using univariable and multivariable logistic regression analyses. Results: The cohort was predominantly middle-aged (62±12 years) men (69%). Patients with plasma cardiac troponin I concentration ≥5 ng/L (n=161) had a higher total (median 33% (IQR 0–47) vs 0% (IQR 0–33)), non-calcified (27% (IQR 0–37) vs 0% (IQR 0–28)), calcified (2% (IQR 0–8) vs 0% (IQR 0–3)) and low-attenuation (1% (IQR 0–3) vs 0% (IQR 0–1)) coronary plaque burden compared with those with concentrations <5 ng/L (n=81; p≤0.001 for all). Low-attenuation plaque burden was independently associated with plasma cardiac troponin I concentration ≥5 ng/L after adjustment for clinical characteristics (adjusted OR per doubling 1.62 (95% CI 1.17 to 2.32), p=0.005) or presence of any visible coronary artery disease (adjusted OR per doubling 1.57 (95% CI 1.07 to 2.37), p=0.026). Conclusion: In patients with acute chest pain but without myocardial infarction, plasma cardiac troponin I concentrations ≥5 ng/L are associated with greater burden of low-attenuation coronary plaque.